Allelopathic Effect of Different Aqueous Extract of Acacia nilotica on Seed Germination and Growth of Wheat (Triticum aestivum) - Dhanai, Chatar Singh; Bharsakle, Lokesh; Singh, Charan (Indian Forester, 2013)
Acacia nilotica commonly known as babul, kikar or Indian gum arabic tree, has been recognized worldwide as a multipurpose tree. Aqueous extracts of fresh leaf, bark and pod of Acacia nilotica were tested for potential effects on Wheat (Triticum aestivum). Aqueous extract of A. nilotica was prepared by soaking 200 gm of powder in 1000 ml distilled water (20%) as per standard method. It was diluted to 5%, 10%, 15%, 20% concentration. The experiment was conducted in sterilized petri dishes for seed germination and growth parameters. The results on seed germination and shoot-root length indicated that the inhibitory effect was proportionate to the concentration of the extracts. Seed germination and shoot-root length of wheat was found to be significant and aqueous effect increased with increasing in the concentration of aqueous fresh leaf, pod and bark extract from 5 to 20 per cent. Inhibitory effect was much pronounced on shoot length ratherthan root length. The maximum inhibitory effect among the various parts of Acacia nilotica was observed for pod extract.